Nutrition research methodologies - Lovegrove, Julie; Sharma, Sangita (Professor in aboriginal and global health research); Hodson, Leanne (Ames, Iowa, USA ; Chichester, West Sussex, UK : Wiley-Blackewell, 2015)
A new book in the acclaimed Nutrition Society Textbook Series, Nutrition Research Methodologies addresses the rapidly advancing field of nutrition research. It covers the diverse methodologies required for robust nutritional research to ensure thorough understanding of key concepts, both for students at undergraduate and postgraduate levels and for scientists working in nutrition research.Combining theory with practical application, Nutrition Research Methodologies addresses both traditional research methods and new technologies, and focuses on a range of complex topics, including energy comp.
Nature, purpose, and implications of research in nutrition / Alan Jackson, Stephen A. Wootton, Martin Wiseman -- Study design : population based studies / Janet Cade and Jayne Hutchinson -- Study design : intervention studies / Jayne V. Woodside, Robert W. Welch, Chris C. Patterson, and Michelle C. McKinley -- Methods to determine dietary intake / Nadia Slimani, Heinz Freisling, Anne-Kathrin Illner, and Inge Huybrechts -- Food composition / Barbara Burlingame and Ruth Charrondiere -- Biomarkers of intake / Gunter Kuhnle -- Methods of data analysis / Graham Horgan -- Considerations when including ethnically diverse population groups in nutrition research / Maria J. Maynard -- Use of biobanks in nutrition research / Kurt Zatloukal, Pieter vant Veer, Christian Viertler, Marc Jeroen, and Peter Hollman -- Methods investigating food related behaviour / Monique Raats, Liisa Lahteenmaki, and Moira Dean -- Methods for assessing nutritional status and body composition / Peter Murgatroyd, Les J.C. Bluck, and Laura Watson -- Energy expenditure and intake methods / Klaas R. Westerterp -- Application of "omics" technologies / Helen Roche, Baukje De Roos, and Lorraine Brennan -- Epigenetics / John C. Mathers -- Nutrient-gene interactions / Anne Marie Minihane -- Data analytical methods for the application of systems biology in nutrition / Corrado Priami and Melissa J. Morine -- Stable isotopes in nutrition research / Margot Umpleby and Barbara A. Fielding -- Animal models in nutrition research / Andrew M. Salter -- Cellular models in nutrition research / Kathleen M. Botham -- Translation of nutrition research / Judith Buttriss.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Nutrition -- Research -- Methodology; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Medical; Nutrition -- Research -- Methodology; Biomedical Research -- methods; Nutritional Physiological Phenomena; Models, Biological; Research Design; Electronic books; Electronic books